STUDY OF ULTRAVIOLET SOLAR RADIATION IN DUHOK CITY UNDER CLEAR SKY CONDITIONS - Omar Salih Omar; Thabit Elias Basheer (Zanco Journal of Pure and Applied Sciences, 2022)
This work focused on the UV solar radiation measurements under clear sky conditions for typical days in months (April to July) when the UV radiation is expected to have the highest values in Duhok city. Two types of UV, (UVA and UVB) were measured from April to July under clear sky conditions. The maximum UVA (wavelength 315-400 nm) irradiance (38 and 37) W/m2 was measured at noon in June and July, respectively. The minimum UVA of 30 W/m2 was recorded at April noon. In July, the hourly UVA ranged between 2.6 W/m2 at 6:00 pm to 37 W/m2 at 12:00 pm; maximum UVB (wavelength 280-315 nm) irradiance of 1.9 W/m2 was measured in July noon’s, and a minimum of 1.4 W/m2 at April noon. The effect of the atmosphere (solar zenith angle) on the UVB clearness index was investigated and a functional relationship between them was developed. Finally, the time required for UVB minimum erythemal dose was estimated.